The lichen genus Psoromidium (Pannariaceae) re-evaluated, with nomenclatural notes on Degeliella and Psoromaria. (9th September 2015) - Unknown
Abstract: Molecular studies have shown that Psoromidium is well separated from Psoromaria and Degeliella, when including the type species only. The latter generic name is illegitimate and the correct name for the other species sometimes included in Psoromidium is shown to be Psoromaria versicolor (Müll. Arg.) P. M. Jørg. & H. L. Andersen, comb. nov. It is the type species of the genus Psoromaria Nyl. ex Hue. The inclusion of Degeliella rosulata in Psoromaria is unresolved, according to the molecular evidence. However, its characters (except the photobiont) match those of Psoromaria, rather than those of the other species with which it groups. So for nomenclature reasons it is transferred to this genus, as Psoromaria rosulata (P. M. Jørg. & D. J. Galloway) P. M. Jørg. & H. L. Andersen comb. nov.